Vascular plant‐mediated controls on atmospheric carbon assimilation and peat carbon decomposition under climate change. (17th April 2018) - Gavazov, Konstantin; Albrecht, Remy; Buttler, Alexandre; Dorrepaal, Ellen; Garnett, Mark H.; Gogo, Sebastien; Hagedorn, Frank; Mills, Robert T. E.; Robroek, Bjorn J. M.; Bragazza, Luca
Abstract: Climate change can alter peatland plant community composition by promoting the growth of vascular plants. How such vegetation change affects peatland carbon dynamics remains, however, unclear. In order to assess the effect of vegetation change on carbon uptake and release, we performed a vascular plant‐removal experiment in two Sphagnum ‐dominated peatlands that represent contrasting stages of natural vegetation succession along a climatic gradient. Periodic measurements of net ecosystem CO2 exchange revealed that vascular plants play a crucial role in assuring the potential for net carbon uptake, particularly with a warmer climate. The presence of vascular plants, however, also increased ecosystem respiration, and by using the seasonal variation of respired CO2 radiocarbon (bomb‐ 14 C) signature we demonstrate an enhanced heterotrophic decomposition of peat carbon due to rhizosphere priming. The observed rhizosphere priming of peat carbon decomposition was matched by more advanced humification of dissolved organic matter, which remained apparent beyond the plant growing season. Our results underline the relevance of rhizosphere priming in peatlands, especially when assessing the future carbon sink function of peatlands undergoing a shift in vegetation community composition in association with climate change. Abstract : By means of a plant‐removal manipulation along a climatic gradient, we demonstrate the importance of vascular plants for maintaining high potential carbon assimilation rates in peatlands under warmer climate. Furthermore, we detected a significant contribution of vascular plants to rhizosphere priming of soil organic matter loss, which extended beyond the peak plant growing season. Our experimental evidence is based on the radiocarbon signature of ecosystem respiration and the humification degree of dissolved organic matter. Our findings provide novel understanding to the mechanisms driving carbon accumulation in peatlands under warmer climate and higher vascular plant abundance.